Historical Study of MTsN 2 Deli Serdang: Development and Its Influence on Student Character Formation - M. Hasan Ishfi; Zaini Dahlan; Mas Teguh Wibowo; Dia Ayu Khairani (al-Afkar, Journal For Islamic Studies, 2026)
This study explores the history and development of MTsN 2 Deli Serdang and its influence on shaping students' character. MTsN 2 Deli Serdang was established in 1994 with the vision of becoming an Islamic educational institution that excels in fostering a generation of morally upright individuals. The research employs a historical approach, utilizing document analysis and in-depth interviews to understand the role of the madrasa in addressing the challenges of character education in the modern era. The findings reveal that the madrasa consistently integrates Islamic values into its curriculum, extracurricular activities, and Islamic learning environment. The urgency of this study lies in the increasing challenges of globalization, which threaten to erode Islamic values in shaping the character of younger generations. This madrasa plays a vital role in shaping a generation that is not only academically competent but also possesses strong Islamic character by balancing knowledge and religious education. Through innovative and adaptive teaching methods, MTsN 2 Deli Serdang remains relevant in providing quality education, supported by exemplary teachers, family involvement, and community engagement. As a solution to the challenges of character development in the modern era, the madrasa combines traditional approaches with modern learning technologies without neglecting religious values. Activities such as worship routines, tahfiz programs, and extracurricular activities based on Islamic values effectively build students’ character. The madrasa also actively forges relationships with the community through social activities that strengthen students' roles as beneficial individuals within their communities. This study is expected to serve as a model for the development of Islamic education in Indonesia, particularly in shaping a young generation with strong character and high integrity. MTsN 2 Deli Serdang demonstrates that Islamic value-based education can provide a holistic solution in nurturing a generation ready to face global challenges without losing their Islamic identity. Through consistent and innovative approaches, the madrasa contributes to creating individuals who are excellent, morally upright, and capable of making positive impacts in various aspects of life.